The Impact of Childhood Health on Adult Labor Market Outcomes - Smith, James P (The Review of Economics and Statistics, 2009)
This paper examines impacts of childhood health on socioeconomic status (SES) outcomes observed during adulthood: levels and trajectories of education, family income, household wealth, individual earnings, and labor supply. The analysis is conducted using panel data that collect these SES measures using a sample who were originally children and are now well into their adult years. Since all siblings are in the panel, unmeasured family and neighborhood background effects can be controlled for. With the exception of education, poor childhood health has a quantitatively large effect on all of these outcomes. Moreover, these estimated effects are larger when unobserved family effects are controlled.